2019
DOI: 10.1057/s41284-019-00171-z
|View full text |Cite
|
Sign up to set email alerts
|

The rating model of corporate information for economic security activities

Abstract: Industrial technology outflow incidents negatively affect corporations, the industry, and countries. Yet, corporate information security is weak, and there is low awareness of the issue's seriousness. This study developed a rating model that can distinguish "importance" based on an objective standard. Fourteen components that can evaluate the importance of corporate information were derived from the related literature and verified for validity and reliability using factor analysis to organize final rating fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Literature [17] analyzed the information popularity growth pattern of YouTube videos and Digg stories and found that there is a strong logarithmic relationship between early and early popularity and future popularity. Literature [18] considers the amount of forwarding caused by external indirect attention users, based on the traditional Susceptible-Infected-Susceptible (SIS) model, newly added the external access state E (External), constructs the infectious disease SISE propagation model, and extracts each time sequence. According to the value of the corresponding state, train the model to find the infection rate, realize the prediction of the number of forwarding, and sense the change of the information popularity situation.…”
Section: Related Workmentioning
confidence: 99%
“…Literature [17] analyzed the information popularity growth pattern of YouTube videos and Digg stories and found that there is a strong logarithmic relationship between early and early popularity and future popularity. Literature [18] considers the amount of forwarding caused by external indirect attention users, based on the traditional Susceptible-Infected-Susceptible (SIS) model, newly added the external access state E (External), constructs the infectious disease SISE propagation model, and extracts each time sequence. According to the value of the corresponding state, train the model to find the infection rate, realize the prediction of the number of forwarding, and sense the change of the information popularity situation.…”
Section: Related Workmentioning
confidence: 99%
“…The literature [17] combined rough set theory with unascertained measure theory, DS evidence theory, and neural network, respectively, so as to realize quantitative evaluation of information system security assurance capabilities and security level protection evaluation and improve the reliability of risk assessment. The literature [18] combined gray theory and fuzzy theory, comprehensively applied the degree of membership and gray to the evaluation, and built a gray fuzzy comprehensive evaluation model to achieve the classification of information system risk levels. The literature [19] proposed a risk assessment method based on fuzzy cognitive maps, which uses fuzzy cognitive maps to obtain the relationship between assets and obtains the system's risk value through the inference process.…”
Section: Related Workmentioning
confidence: 99%
“…An analysis of scientific publications showed that the issues of the impact of environmental, social and governance risks on company performance are the subject of many studies by foreign scientists such https: //doi.org/10.15405/epsbs.2020.04.84 Corresponding Author: T. Korneeva Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 664 as: Deng and Xiang (2019), Ionescu, Firoiu, Pirvu, and Vilag (2019), Bernardi and Stark, (2018), Khan (2019), Rodríguez-Fernández, Sánchez-Teba, López-Toro, and Borrego-Domínguez (2019) etc. The issues of economic security of companies were considered in the works of the following authors: Kalashnikova, Tatarovskaya, and Tselniker (2019), Na, Park,Yu, Kim, and Chang (2019), and others.…”
Section: Problem Statementmentioning
confidence: 99%